2019
DOI: 10.3390/w11122481
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Management in Citrus Processing Industries: An Overview of Advantages and Limits

Abstract: Citrus-processing industries produce large volumes of wastewater (CPWW). The large variability of these volumes coupled to physicochemical characteristics of CPWW determine severe constraints for their disposal due to both economic and environmental factors. To minimize the management costs and prevent the negative ecological impacts of CPWW, several systems have been proposed and adopted. However, all these treatment/valorization routes have many issues that are not yet thoroughly known by the scientific comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 69 publications
(119 reference statements)
1
29
0
Order By: Relevance
“…In particular, Corsino et al [38] observed that as the OLR increased there was a proportional increase in the abundance of filamentous bacteria. Similar results were also obtained by Zema et al [44], confirming that high OLR determined the onset of process instability, especially in terms of worsening of the sludge settling characteristics due to the overgrowth of filamentous bacteria as will be better discussed in the following paragraphs.…”
Section: Figsupporting
confidence: 86%
“…In particular, Corsino et al [38] observed that as the OLR increased there was a proportional increase in the abundance of filamentous bacteria. Similar results were also obtained by Zema et al [44], confirming that high OLR determined the onset of process instability, especially in terms of worsening of the sludge settling characteristics due to the overgrowth of filamentous bacteria as will be better discussed in the following paragraphs.…”
Section: Figsupporting
confidence: 86%
“…Another viable system for SW treatment is the anaerobic digestion, which allows an easier control of the main operational parameters of the depuration process. The anaerobic digestion systems are used for depurating several agro-industrial waste and wastewater, such as the olive mill wastewater or citrus peel waste and wastewater [20][21][22]. However, the methane production in the anaerobic digestion plants treating SW is often reduced or even inhibited by the high ammonia content (often over 4.0 g L −1 ) that hampers the activity of the methanogenic bacteria [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Reusing wastewater can assist boost water reserves for agriculture, which will help fertilize agricultural regions and address the current water deficit brought on by the drought (Zema et al, 2019). According to (Mojiri and Abdul Aziz, 2011) and (Banitalebi et al, 2016) in contrast to river water, using wastewater for irrigation does have fullsize capabilities: it reduces strain on the underground water resources, will increase agricultural procedure efficiency, decreases wastewater price of treatment, enhances soil permeability, enhances permeability, lowers bulk density, and lowers pH saline soil.…”
Section: Wastewater Uses Especially In Irrigationmentioning
confidence: 99%
“…The soil structure, bodily soil characteristics, soil water storage ability can, fertility and natural counted content material all be increased with wastewater remedy (Arast et al, 2018). The scarcity of precipitation, the occurrence of inadequate water distribution systems, the excessive demand for agricultural water and reduced irrigation effectiveness, insufficient sewage treatment, and local weather variability are all contributing contributors to the water deficit, in accordance to Zema et al, (2019). Using domestic wastewater in agriculture is one option of discarding of and managing wastewater (Malekian et al, 2008).…”
Section: Wastewater Uses Especially In Irrigationmentioning
confidence: 99%